Position and Role of Sharia Banks on Murâbahah Contract Implementation - Rahman, Muh. Fudhail; Humaira, Aida (Madania: Jurnal Kajian Keislaman, 2019)
The legality and validity of sharia banks still somehow lead to some problems, including a negative view of the use of murâbahah contract at the level of practice in the field. Is it true that the application of the sale and purchase agreement of sharia banks, in this case the contract of murâbahah, salam and istisnâ’, is essentially a sale and purchase process? This is a critical question in this research. This is a critical question in this research. Such a miserable view not only emerged in the country, but also voiced in several other Muslim countries. This type of research is a qualitative descriptive method with content analysis of qualitative / inductive data. Data sources are the results of interviews with Sharia Commercial Banks (BUS) BNI, Sharia Business Units (UUS) Permata Syariah and Sharia People's Credit Banks (BPRS) Al-Salam. This research shows that sharia banks which are still dominant in using murâbahah contracts are not appropriate. Judging from the aspect of sharia maqâsid, the position of shariah banks is basically outwardly not acting as a provider of goods. Sharia banks do not have a stock of goods as a meaning of the use of contracts based on exchange or sale and purchase transactions. In fact, the position and position of a sharia bank is essentially only as an institution mediating financial service providers and not sellers. However, from the perspective of jurisprudence the practice of murâbahah in Sharia Financial Institutions (LKS)  has fulfilled the pillars and conditions, but in the absence of stock of goods, the sale and purchase transactions of sharia banks seem still as al-makhârij al-shar'î (sharia solutions). Legalitas dan keabsahan bank syariah masih menyisakan masalah. Termasuk pandangan negative tentang penggunaan akad murâbahah pada tataran praktek di lapangan. Benarkah bahwa aplikasi akad jual beli bank syariah, dalam hal ini akad murâbahah, salam dan istisnâ’, secara hakiki telah terjadi jual beli?.  Inilah pertanyaan kritis dalam penelitian ini. Pandangan miris ini tidak hanya muncul di tanah air, tapi juga disuarakan di beberapa negara muslim lainnya. Jenis penelitian ini adalah deskriptif kualitatif dengan metode content analisis terhadap data-data yang bersifat kualitatif/induktif. Sumber data adalah hasil wawancara kepada Badan Usaha Syariah (BUS) BNI, Unit Usaha Syariah (UUS) Permata Syariah,  dan Bank Perkreditan Rakyat Syariah (BPRS) Al-Salam. Penelitian ini menunjukkan bahwa bank syariah yang saat ini masih dominan menggunakan akad murâbahah adalah kurang pas. Dikaji dari aspek maqâsid syariah, posisi bank syariah pada dasarnya secara lahiriyah tidak bertindak sebagai  penyedia barang. Bank syariah tidak memiliki stock barang sebagai pemaknaan terhadap penggunaan akad-akad yang berbasis pada transaksi tukar-menukar atau jual beli. Sebenarnya, kedudukan dan posisi bank syariah hakekatnya adalah hanya sebagai institusi mediator penyedia jasa keuangan dan bukan penjual. Namun, dari sudut fikih praktek murâbahah di Lembaga Keuangan Syariah (LKS) sudah memenuhi rukun dan syarat, tapi dengan tidak adanya stock barang, maka transaksi jual beli bank syariah terkesan masih sebagai al-makhârij al-shar'î  (solusi syariah).